Evaluation the effect of irrigation water salinity and Fusarium fungi on seven safflower cultivars (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
In order to study the effect of Salinity levels of Sodium chloride and Soil type on the characteristics of some grown seeds and the resistance rate of Fusarium fungi (quantitative length evaluation of necrotic part in plants gorget) in biotypes of safflowers, an experiment was factorically conducted by using two salinity levels of sodium chloride (20% and 50% salinitys), seven biotypes of acanaceous and non-acanaceous safflowers (Iraqi 222, IL111, K.H.64.68, and Varamin 295,Local Isfahan , Padideh and 340779), two types of soil (clay sandy-clay), in a three times randomized complete block design. The variance analyzing results showed that between the levels of all factors, there was meaningful difference for 2 studied characteristics. According to the results obtained from the comparison of factors means, genotypes of Iraqi 222, K.H.64.68 and 340779 under the condition of 20% salinity and genotype of Iraqi 222 under the condition of 50% salinity contained the most numbers of grown seeds. On the other hand the most resistance rate against Fusarium mushrooms was related to genotype K.H.64.68 under the condition of clay soil and 20% salinity, genotype IL111 under the condition of clay soil and 50% salinity and local genotype of Isfahan under the condition of sandy-clay soil with 20% salinity, Based on the results obtained from the linear regression and simple correlation coefficient there was positive and meaningful correlation between two evaluated characteristics in the probability level of 1% and the relation between them was estimated as linear and positive one (y=0/545+0/234X), where X refers to the number of grown seeds and y refers to the resistance against Fusarium.